Chopin's Dream as Reality: A Critical Reading of Eternal Sonata - Quijano-Cruz, Johansen (Eludamos: Journal for Computer Game Culture, 2009)
This article opens with a short statement on how video games should be considered as a viable means of making cultural and social statements and compares the evolution of literature to the evolution of video game narratives. After making an argument for Eternal Sonata as meaningful art worthy of critical attention it proceeds to give a critical reading of the game which presents Eternal Sonata as an instrument critical of specific aspects of society, including war, human greed, and the interests of large companies. The article integrates video game and critical theory, professional commentary, excerpts from the game, and examples of poetry, music, and painting to support the arguments presented.